1992
DOI: 10.1104/pp.98.4.1255
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Nitrate Reductase mRNA Levels by Cytokinin-Abscisic Acid Interactions in Etiolated Barley Leaves

Abstract: To investigate the mechanisms by which the expression of a specific gene may be modulated by multiple hormones, the regulation of nitrate reductase (NR) mRNA levels by cytokinin and abscisic acid (ABA) was studied in etiolated barley (Hordeum vulgare L. cv Robust) leaves using a barley NR cDNA as a probe. Northem blot analyses of the levels of NR mRNA indicate that accumulation of the mRNA was enhanced by the cytokinin, benzyladenine (BA), and suppressed by ABA and that the hormonal effects on NR gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 26 publications
(26 reference statements)
3
36
0
Order By: Relevance
“…Pgkl mRNAs accumulate in leaves in response to cytokinin (6-BAP) treatment. Although cytokinins have been implicated in a wide variety of plant responses, including transcriptional activation of nitrate reductase (Lu et al, 1990(Lu et al, , 1992 and PEPC (Suzuki et al, 1994) and increases in PEPC and NADP-malic enzyme accumulation and activity in the ice plant (Dai et al, 1994), their role in controlling gene expression in response to osmotic stress is still not fully understood. One possibility is that cytokinin response elements interact with cytokininactivated transcription factors (Thomas et al, 1995) to mediate transcriptional activation events.…”
Section: Discussionmentioning
confidence: 99%
“…Pgkl mRNAs accumulate in leaves in response to cytokinin (6-BAP) treatment. Although cytokinins have been implicated in a wide variety of plant responses, including transcriptional activation of nitrate reductase (Lu et al, 1990(Lu et al, , 1992 and PEPC (Suzuki et al, 1994) and increases in PEPC and NADP-malic enzyme accumulation and activity in the ice plant (Dai et al, 1994), their role in controlling gene expression in response to osmotic stress is still not fully understood. One possibility is that cytokinin response elements interact with cytokininactivated transcription factors (Thomas et al, 1995) to mediate transcriptional activation events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the enhancement of the levels of NR mRNAs by cytokinins has been shown to be regulated transcriptionally (Lu et al, 1990(Lu et al, , 1992, but the cytokinin enhancement of the levels of LHCP mRNAs has been shown to be regulated posttranscriptionally Tobin, 1986, 1989). The products of these genes could be categorized as appendages, of which gene expression is inducible in nature in responding to environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cytokinins also regulate the expression of various genes. In the cases of Rubisco small subunit (Lerbs et al, 1984;Funckes-Shippy and Levine, 1985;Flores and Tobin, 1989), LHCP Tobin, 1986, 1989), and NR (Lu et al, 1990(Lu et al, , 1992, up-regulation of the gene expression by cytokinins is considered to be due to an increase in rate of gene-specific transcription and/or an increase in mRNA stability. It is well known that changes in N availability strongly affect the level of cytokinins, which are thought to be synthesized in roots at least at the vegetative stage of higher plants (Feldman, 1975).…”
mentioning
confidence: 99%
“…Light signals at red/far-red (Rajasekhar et al, 1988;Melzer et al, 1989) and at blue (Melzer et al, 1989) regions of the spectrum both increase the NR mRNA levels of etiolated seedlings. Cytokinin enhances, whereas ABA suppresses, the light induction of NR transcription in etiolated barley leaves (Lu et al, 1990(Lu et al, , 1992. The biological significance of light signal and hormonal regulation is unclear.…”
Section: Rp07035-25 and Gm46116 Jb Was Supported By Nih Geneticsmentioning
confidence: 99%